Effects of galU Mutation on Pseudomonas syringae–Plant Interactions - Deng, Wen-Ling; Lin, Yuan-Chun; Lin, Rong-Hwa; Wei, Chia-Fong; Huang, Yi-Chiao; Peng, Hwei-Ling; Huang, Hsiou-Chen (Molecular plant-microbe interactions, 2010)
Bacterial galU coding for a uridine diphosphate-glucose pyrophosphorylase plays an important role in carbohydrates biosynthesis, including synthesis of lipopolysaccharides (LPS), membrane-derived oligosaccharides, and capsular polysaccharides. In this study, we characterized the galU mutant of Pseudomonas syringae pv. syringae 61 (Psy61), a necrotizing plant pathogen whose pathogenicity depends on a functional type III secretion system (T3SS), and showed that the Psy61 galU mutant had reduced biofilm formation ability, was nonmotile, and had an assembled T3SS structure but failed to elicit hypersensitive response in resistant plants and necrotic lesions in susceptible plants. Moreover, the defective LPS and other pathogen-associated molecular patterns (PAMPs) on the surface of the Psy61 galU mutant were capable of inducing PAMP-triggered immunity, which severely compromised the ability of the Psy61 galU mutant to survive in planta. Our results demonstrated that the complete LPS protected plant-pathogenic bacteria from host innate immunity, similar to what was found in animal pathogens, prior to the translocation of T3S effectors and bacterial multiplication.